Policy Issues and Prospects for the Development of China's Long-term Care Insurance System: Taking Shanghai as an Example - Guo, Wenxian; Qin, Chenyi; Shi, Zhongyu (Transactions on Social Science, Education and Humanities Research, 2024)
At present, Shanghai is the earliest city that entered the aging society and the large city with the highest aging degree in China. Over the past 30 years, the total number of elderly population in Shanghai has increased dramatically and the degree of aging has developed rapidly. The current long-term care (LTC) insurance policy has been piloted in Shanghai for six years. This paper understands and analyses the current situation of LTC insurance in Shanghai from various aspects related to LTC insurance, and provides a strategic direction for improving LTC insurance from the level of service and policy formulation. In February 2024, the project team selected family members of LTC insurance beneficiaries in Qianzhong Village, Fengxian District, Shanghai (n=13), relevant healthcare workers (n=3), and the secretary of the village committee and the leadership team of Wufang Village (n=2) to conduct face-to-face and telephone interviews and surveys, which included satisfaction with the LTC insurance, the degree of ease of handling, the level of service, problems, and suggestions, and the interviews lasted for half an hour. The content of the interviews was recorded, transcribed into text, summarised to generate themes, and finally concluded based on the statements of representative interviewees. According to the three types of interviews, long-term care insurance is convenient and well-received in terms of processing, service, and policy evaluation. However, there are problems such as uneven levels of carers, high cost of institutional care, and mismatch between home and institutional care needs. Recipients anticipate additional government policies since they require long-term care insurance services urgently for serious illnesses. In the future, it will be essential to enhance caregiver education, enhance the way that care expenses are reimbursed, and optimize service offerings to better serve the requirements of various families and support the long-term care insurance system's growth.